Post-translational hydroxylation by 2OG/Fe(II)-dependent oxygenases as a novel regulatory mechanism in bacteria - van Staalduinen, Laura M.; Jia, Zongchao (Frontiers in Microbiology, 2015)
Protein hydroxylation has been well-studied in eukaryotic systems. The structural importance of hydroxylation of specific proline and lysine residues during collagen biosynthesis is well established while, recently, key roles for post-translational hydroxylation in signalling and degradation pathways have been discovered. The function of hydroxylation in signalling is highlighted by its role in the hypoxic response of eukaryotic cells, where oxygen dependent hydroxylation of the hypoxia inducible transcription factor both targets it for degradation and blocks its activation. In contrast, the role of protein hydroxylation has been largely understudied in prokaryotes. Recently, an evolutionarily conserved class of ribosomal oxygenases (ROX) that catalyze the hydroxylation of specific residues in the ribosome has been identified in bacteria. ROX activity has been linked to cell growth, and has been found to have a direct impact on bulk protein translation. This discovery of ribosomal protein hydroxylation in bacteria could lead to new therapeutic targets for regulating bacterial growth, as well as, shed light on new prokaryotic hydroxylation signalling pathways. In this review, recent structural and functional studies will be highlighted and discussed, underscoring the regulatory potential of post-translational hydroxylation in bacteria.